Gender-Based Violence During COVID-19 Pandemic: A Mini-Review - Mittal, Shalini; Singh, Tushar (Frontiers in Global Women's Health, 2020)
Purpose: Quarantine is necessary to reduce the community spread of the Coronavirus disease, but it also has serious psychological and socially disruptive consequences. This is known as the quarantine paradox that also includes a surge in the cases of gender-based violence. However, there exists a clear gap of rigorous literature exploring the issue. Hence, the current paper attempts to understand gender-based violence as an aspect of the COVID-19 lockdown. It reviews the pattern of rise in gender violence cases and the resultant psychological and social issues and attempts to create awareness by initiating a discourse urging for change in the response towards the victims of gender-based violence. The paper further attempts to suggest measures to mitigate the issues arising out of gender violence during quarantine. Method: The current paper reviews the literature on the rise of gender-based violence in the times of current and past pandemics. The paper also reviews the published reports in scientific as well as mass media literatures focusing on the rise of gender-based violence during the imposed lockdown, its consequences, and the measures taken by the governments to tackle the issue. Results: The present review reveals that similar to the previous pandemics and epidemics, there has been an alarming rise in the incidents of gender-based violence during the COVID-19 pandemic. The present review further reveals various other risk factors that have been found attributive to the surge of gender-based violence such as economic insecurity and alcohol consumption. The results of the review indicate that despite its global prevalence, gender-based violence has been one of the most neglected outcomes of pandemics. Moreover, the legislatures and services available for such victims are often inadequate and, thus, worsening their situation. Conclusion: Pandemic situations have been found to be associated with advancements in the medical field. However, a part and parcel of this situation is the age-old practice of quarantine that has several negative outcomes. This also includes a surge in gender-based violence that raises serious concerns about the safety of women. As the legislatures provided and measures taken by the governments are falling short in dealing with the issue, a number of non-government organizations are stepping up to provide necessary services to these victims.